Physiological and Pathological Functions of SLC26A6 - Wang, Juan; Wang, Wenkang; Wang, Hui; Tuo, Biguang (Frontiers in Medicine, 2021)
Solute Carrier Family 26 (SLC26) is a conserved anion transporter family with 10 members in human (SLC26A1-A11, A10 being a pseudogene). All SLC26 genes except for SLC26A5 (prestin) are versatile anion exchangers with notable ability to transport a variety of anions. SLC26A6 has the most extensive exchange functions in the SLC26 family and is widely expressed in various organs and tissues of mammals. SLC26A6 has some special properties that make it play a particularly important role in ion homeostasis and acid-base balance. In the past few years, the function of SLC26A6 in the diseases has received increasing attention. SLC26A6 not only participates in the development of intestinal and pancreatic diseases but also serves a significant role in mediating nephrolithiasis, fetal skeletal dysplasia and arrhythmia. This review aims to explore the role of SLC26A6 in physiology and pathophysiology of relative mammalian organs to guide in-depth studies about related diseases of human.